Develamiento de la Galería de las Decanas y los Decanos de la Facultad de Ciencias de la Salud y del Ser Humano de la UEB - DANNY LLIVI RUILOVA (2024)
At the Center for National and International Events (CENI), the Unveiling of the Gallery of the Deans of the Faculty of Health and Human Sciences of the UEB took place; the same one that was attended by Dr. Arturo Rojas Sánchez, Rector UEB; Dr. Silvia Pacheco Mendoza, Academic Vice-Rector; Dr. Carlos Ribadeneira Zapata, Vice-Rector for Research and Liaison; Dr. Silvana López Paredes, Dean; teaching staff and special guests.